2010
DOI: 10.1111/j.1742-4658.2009.07504.x
|View full text |Cite
|
Sign up to set email alerts
|

From meiosis to postmeiotic events: The secrets of histone disappearance

Abstract: One of the most obscure phenomena in modern biology is the near genome‐wide displacement of histones that occurs during the postmeiotic phases of spermatogenesis in many species. Here we review the literature to show that, during spermatogenic differentiation, three major molecular mechanisms come together to ‘prepare’ the nucleosomes for facilitated disassembly and histone removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
119
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(127 citation statements)
references
References 40 publications
(57 reference statements)
2
119
0
6
Order By: Relevance
“…H1.4K34ac levels are high in the majority of immature germ cells (spermatogonia) and meiotic spermatocytes, but disappear at the postmeiotic round spermatid stage. Interestingly, we observed high levels of H1.4K34ac in the elongating spermatids (coinciding with chromatin reorganization) (Gaucher et al 2010) and a loss of signal in condensing spermatids and spermatozoa (Fig. 4A,B).…”
Section: H14k34ac Shows a Dynamic Behavior During Human Spermatogenementioning
confidence: 96%
See 1 more Smart Citation
“…H1.4K34ac levels are high in the majority of immature germ cells (spermatogonia) and meiotic spermatocytes, but disappear at the postmeiotic round spermatid stage. Interestingly, we observed high levels of H1.4K34ac in the elongating spermatids (coinciding with chromatin reorganization) (Gaucher et al 2010) and a loss of signal in condensing spermatids and spermatozoa (Fig. 4A,B).…”
Section: H14k34ac Shows a Dynamic Behavior During Human Spermatogenementioning
confidence: 96%
“…Dramatic changes in chromatin structure and in core histone modifications also occur during spermatogenesis: In maturating spermatids, histones are replaced by transition proteins and, later on, protamines (Gaucher et al 2010). To study this differentiation process, we performed immunohistochemistry of biopsies from human testis and found that H1.4K34ac shows a dynamic behavior during spermatogenesis ( Fig.…”
Section: H14k34ac Shows a Dynamic Behavior During Human Spermatogenementioning
confidence: 99%
“…Compared with standard histones, histone variants have a lower degrees of stability. [30] In testis, in addition to testis-specific histone variants, somatic histone variants are also expressed. In mature sperm, the most frequently testis-specific histone H2B is found.…”
Section: Sperm Histone Modificationmentioning
confidence: 99%
“…They involve in 12., and 13. stages of spermatogenesis, but leave the process at 14. stage. [30] These proteins stick to DNA, and thus play critical roles in separation of histone variants, and later condensation by protamine. [46] Then TPs are totally replaced by protamines.…”
Section: Modification Of Chromatin During Spermatogenesismentioning
confidence: 99%
“…Le fait marquant de cette différenciation post-méiotique est la disparition des nucléosomes 1 , unités universelles d'organisation et d'empaquetage des génomes chez les eucaryotes. La disparition des histones, les constituants des nucléosomes, au cours de la spermiogenèse et leur remplacement par des petites protéines basiques nonhistones, les protéines de transition et les protamines ont été précédemment décrits [1]. Cette transformation globale de l'organisation du génome dans les cellules germinales mâles a comme objectif la compaction extrême de celuici avant le voyage du spermatozoïde afin d'assurer sa protection lors de cette période à risque pour son intégrité.…”
unclassified